Pendampingan Eksplorasi Diri Praremaja untuk Penguatan Karakter Bangsa di SDN Dukuh Mencek 04, Jember - Ajeng Rusti Anti; Ferentika Noftrianda Putri; Shinta Indah Meilia; Keysha Khairani; Moch. Ilham Baharuddin; Saeul Ma’mun; Irliana Faiqotul Himmah; Ghanesya Hari Murti; Bejo Apriyanto; Widowati Widowati; Inayah Swasti Ratih; Agung Nugroho Puspito (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This community service activity was conducted to facilitate pre-adolescent children in recognizing their potential, interests, and talents as a foundation for national character development based on Pancasila values. The mentoring was carried out through systematic observation of 20 fifth-grade students at Dukuh Mencek 04 Public Elementary School in Jember. The approach was designed to develop self-confidence, social skills, and the ability to formulate life goals from an early age. Observations focused on aspects of responsibility, cooperation, mutual respect, and students' tendencies in interests and talents. The observation results show that targeted mentoring helps students recognize their personal strengths more clearly, increases participation in group activities, and cultivates awareness of character values relevant to self-development. The findings confirm that self-recognition mentoring at pre-adolescent age has the potential to be an effective strategy for building competitive young generation characters grounded in Pancasila values.